2011
DOI: 10.1248/bpb.34.1542
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Extracellular-Signal Regulated Kinase by Epidermal Growth Factor Is Potentiated by cAMP-Elevating Agents in Primary Cultures of Adult Rat Hepatocytes

Abstract: Epidermal growth factor (EGF) is well recognized as a potent mitogen, and appears to trigger liver regeneration after partial hepatectomy or after acute liver cell necrosis caused by chemicals in vivo. [1][2][3][4] The response of adult rat hepatocytes to EGF has also been extensively investigated with respect to DNA synthesis and proliferation in vitro. EGF is now known to be a potent hepatocyte mitogen and induces multiple biological activities in a wide variety of cell types. [5][6][7][8] More recently, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 58 publications
(75 reference statements)
1
5
0
Order By: Relevance
“…Our findings show, for the first time, that both PKA inhibitors are capable of negating the stimulatory effect of cAMP analogue on OT and VP secretion from the rat H-NH system. This observation is in agreement with those of previous stu dies demonstrating the ability of H-89 and/or cAMPS-Rp to antagonise various effects of cAMP/PKA stimulators under a range of experimental conditions [25,26,28,29]. For example, H-89 antagonised the effect of 8-Br-cAMP on epidermal growth factor (EGF)-induced ERK2 phosphorylation in primary cultures of rat hepatocytes [29], while in another study, 8-Br-cAMP and PACAP treatment significantly increased nitric oxide synthase type 1 (NOS1) level in rat pituitary gonadotrophs in vitro, and H-89 was able to inhibit such stimulation [25].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Our findings show, for the first time, that both PKA inhibitors are capable of negating the stimulatory effect of cAMP analogue on OT and VP secretion from the rat H-NH system. This observation is in agreement with those of previous stu dies demonstrating the ability of H-89 and/or cAMPS-Rp to antagonise various effects of cAMP/PKA stimulators under a range of experimental conditions [25,26,28,29]. For example, H-89 antagonised the effect of 8-Br-cAMP on epidermal growth factor (EGF)-induced ERK2 phosphorylation in primary cultures of rat hepatocytes [29], while in another study, 8-Br-cAMP and PACAP treatment significantly increased nitric oxide synthase type 1 (NOS1) level in rat pituitary gonadotrophs in vitro, and H-89 was able to inhibit such stimulation [25].…”
Section: Discussionsupporting
confidence: 93%
“…One such inhibitor is H-89, which has been found to act as a competitive antagonist of ATP at its binding site on the PKA catalytic subunits [20], and to offer great value in discriminating between the effects of PKA and other cAMP-regulated proteins such as EPACs. As a potent PKA inhibitor, H-89 has been found to abolish various effects of cAMP/PKA stimulation by forskolin, PACAP, or 8-Br-cAMP in vitro [21,24,25,28,29]. However, H-89 has also been found to have a range of properties not asso ciated with PKA, and to restrain the activity of several kinases other than PKA, including protein kinase C (PKC), Rho-associated kinase (ROCK-II), extracellular signalregulated kinase 1 and 2 (ERK 1/2), mitogen-activated protein kinase (MAPK), mitogen-and stress-activated protein kinase 1 (MSK1), and ribosomal protein s6 kinase (S6K1) [20,39].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…HTGL release was suppressed by the PKA inhibitors H-89 and KT5720. 24,25) Thus, we investigated whether the release of HTGL involved PKA activity in hepatocytes with or without prazosin treatment. It was observed that intracellular PKA activity increased after treatment with 100 µM prazosin in a time-dependent manner for up to 60 min (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, p70S6K phosphorylation induced by 5-HT or BW723C86 was not affected by an inactive structural analogue of U-73122 U-73343 (10 −6 M), a protein kinase A inhibitor H-89 (10 −6 M), 33) a protein kinase C inhibitor GF109203X (10 −6 M), 34) or a direct adenylate cyclase inhibitor 2,4-dideoxyadenosine (10 −6 M). 35) The proposed mechanism for the induction of hepatocyte DNA synthesis and proliferation via the 5-HT 2B receptor is shown in a schematic in Fig. 6.…”
Section: Effects Of Specific Signal Transduction Inhibitors Downstreamentioning
confidence: 99%